Leadership and HRM: A Review of the Relationship between Leadership Styles and Employee Outcomes - Murugan, Gracy Angel (AG Volumes, 2024)
In order to improve employee performance, "human resource management (HRM)" procedures and suitable leadership are essential. The collection of HR methods that effectively contribute to enhanced employee performance via competent leadership remained a mystery, despite the abundance of research on HRM and leadership. In this article review the various literature’s study on relationship between leadership styles and employee outcomes. This review underscores the significance of leadership styles and HRM practices in shaping employee outcomes. Transformational, servant, shared, and empowering leadership styles enhance motivation, productivity, and commitment, while authoritarian approaches hinder performance. Effective HRM strategies, including training, compensation, and occupational safety and health (OSH), further support employee engagement and retention. SMEs can benefit from leadership styles that foster knowledge sharing and empowerment, contributing to digital leadership development. Although high-involvement HRM practices (HIHRMPs) align with digital HRM strategies, further research is needed to establish a direct link. Ultimately, well-implemented leadership and HRM practices create a positive work environment, driving sustained employee performance and organizational success.